การศึกษาการบริหารครูชาวต่างชาติของโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร A STUDY OF THE MANAGEMENT OF FOREIGN TEACHERS OF PRIVATE BILINGUAL SCHOOLS IN BANGKOK METROPOLIS - จันแดง มัณฑลิน; สุเมตติกุล ปิยพงษ์ (An Online Journal of Education, 2017)
การวิจัยในครั้งนี้เป็นการวิจัยเชิงพรรณนา มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบันและสภาพที่พึงประสงค์ของการบริหารครูชาวต่างชาติของโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร 2) วิเคราะห์ประเด็นการบริหารครูชาวต่างชาติของโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร ตามลำดับความต้องการจำเป็น ประชากรในการวิจัย ได้แก่ ผู้บริหารโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร กลุ่มตัวอย่าง จำนวน 59 โรงเรียน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถามลักษณะเป็นมาตรส่วนประมาณค่า 5 ระดับ ได้รับแบบสอบถามกลับคืนมาคิดเป็นร้อยละ 100 วิเคราะห์ข้อมูลเชิงปริมาณด้วยสถิติบรรยาย ได้แก่ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และข้อมูลเชิงคุณภาพ วิเคราะห์ข้อมูลด้วยการวิเคราะห์เนื้อหา (Content Analysis) และใช้ดัชนีการจัดเรียงลำดับความสำคัญของความต้องการจำเป็น Modified Priority Needs Index (PNI Modified) จัดลำดับความสำคัญของความต้องการจำเป็นในการบริหารครูชาวต่างชาติ ผลการวิจัย พบว่า สภาพปัจจุบันของการบริหารครูชาวต่างชาติของโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร ในภาพรวมและรายด้านทุกด้านอยู่ในระดับปานกลาง สภาพที่พึงประสงค์ในภาพรวมและรายด้านทุกด้านอยู่ในระดับดีมาก เรียงลำดับความต้องการจำเป็นด้วย PNI Modified ได้เป็น 1) ด้านการอบรมภาษาและวัฒนธรรมไทย 2) ด้านการทำสัญญาปฏิบัติงาน 3) ด้านความสามารถในการใช้ภาษาอังกฤษ 3 ด้านนี้เป็นจุดอ่อนควรได้รับการพัฒนา มีจุดแข็งที่ควรได้รับการส่งเสริม 5 ด้าน ได้แก่ 1) ด้านการออกเสียงและการใช้ภาษา 2) ด้านการพัฒนาบุคลากร3) ด้านการร่วมมือและสัมพันธ์กับเพื่อนครู 4) ด้านวุฒิทางการศึกษา 5) ด้านจิตวิทยาและการจัดการเรียนการสอน This descriptive research aimed at studying the current and desirable states, and the priority needs for management of foreign teachers in private bilingual schools in Bangkok. The population of this research included private bilingual school principals with a sample size of 59. A questionnaire with a rating scale was used to collect data at a return rate of 100 percent. A descriptive statistical analysis including frequency, percentage, means, standard deviation and qualitative data. A content analysis and Priority Needs Index (PNI modified) were used to prioritize the requirement of the management of private bilingual schools. The results show the desirable state of management of foreign teachers at a high level when sorted with a PNImodified. They were 1) the training of language and Thai culture, 2) the contracting of the performance employment contract, and 3) the competency at the English language. Therefore, they were considered weaknesses and should be further developed. The other 5 aspects were considered strengths and should be encouraged. These were 1) the skill of speaking and using the English language, 2) the training and development of foreign teachers, 3) the partnership and relationship between foreign teachers and colleague, 4) the degree obtained, and 5) the educational psychology and pedagogy.